Awareness of community about sound sleep, sleep disorders and its implications: a step towards sleep health - Piryani, Rano Mal; Piryani, Suneel; Sijapati, Milesh Jung (Nepalese Respiratory Journal, 2022)
Sleep is a naturally cyclical state of the mind and body. It plays an indispensable role in sustaining the good health of an individual. Inadequate and poor-quality sleep upsets the people of all ages leading to widespread impact on the body and mind. Insufficient sleep can be due either to medical conditions or mental health disorders or sleep disorders. Worldwide, 30%-35% of adults are suffering from insomnia, and about 10% of the population fits in diagnostic criteria for sleep disorders. From 8 countries across Asia and Africa, 17% people reported trouble with their sleep. People have poor knowledge and awareness about the sleep disorders. There is scarcity of trained healthcare professionals and workers in sleep medicine in South Asia; trained and experienced health professionals need to enhance the services of sleep medicine to meet the needs of their population. Creating awareness among the public about sleep and sleep disorders is one of the step towards Sleep Health. It is recommended to the policy makers of countries of South Asia to develop National Sleep Health Policy to address the issue of Sleep Health as lack of sleep or inadequate sleep both in quantity and quality will have impacts on health of the people and consequently economy of the country.